CYBERSECURITY GOVERNANCE IN ELECTRONIC-BASED GOVERNMENT SYSTEMS: AN ANALYSIS OF THE GOVERNMENT’S LEGAL RESPONSIBILITY FOR PUBLIC DATA BREACHES - Erfan Wahyudi; Muhammad Suhardi (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2025)
The increasing digitalisation of public administration has made cybersecurity governance a central issue in electronic-based government systems. Public data breaches in government digital platforms are no longer merely technical incidents, but also raise questions of administrative responsibility, public service continuity, and citizens’ legal protection. This study examines the government’s legal responsibility for public data breaches within the framework of cybersecurity governance and electronic-based government systems. Using a normative juridical method with statutory, conceptual, and analytical approaches, this article analyses cybersecurity as part of the state’s duty to provide secure, reliable, and accountable digital public services. The findings show that government responsibility can be constructed through three layers: preventive responsibility, responsive responsibility, and restorative responsibility. Preventive responsibility requires risk-based cybersecurity standards, institutional coordination, security audits, and adequate backup systems. Responsive responsibility requires rapid incident detection, containment, reporting, and transparent public communication. Restorative responsibility requires service recovery, breach notification, institutional evaluation, and remedies for affected citizens. The novelty of this study lies in integrating cybersecurity governance, electronic-based government systems, and administrative-law responsibility into a single analytical framework. The study argues that public data protection is not only a technical obligation, but also a legal manifestation of due care, accountability, good administration, and public service responsibility. Therefore, cybersecurity governance must be positioned as an essential requirement for lawful, secure, and citizen-centred digital government.